SISTEM INFORMASI PENJUALAN BAJU TSANIA COLLECTION BERBASIS WEBSITE - Novega, Rizallo; Alfianti Oktavia, Chaulina (Jurnal Fakultas Teknologi Informasi, 2023)
Tsania Collection is a small and medium enterprise that specializes in clothing sales. Currently, the system in the Tsania Collection is a manual system that traditionally records transactions and sales. Product updates are also done manually by the seller, namely by uploading via Whatsapp and Facebook status. In addition, the development of Tsania Collection requires owners to be able to provide ordering services for consumers to support sales transactions and better service. The research method that researchers use is the waterfall method. The tool used to draw the system model is IOFC, as well as in the design of information systems using Data Flow Diagrams (DFD), and Conceptual Data Models (CDM). With this information system, it is hoped that it will make it easier for Tsania Collection to manage its products and sales data, and make it easier for customers or prospective customers to make online sales transactions so that they can be done anytime.